Telemedicine in rheumatology: a reliable approach beyond the pandemic. (7th September 2020) - Cavagna, Lorenzo; Zanframundo, Giovanni; Codullo, Veronica; Pisu, Maria Grazia; Caporali, Roberto; Montecucco, Carlomaurizio
Abstract: Objectives: The SARS-CoV-2 outbreak has imposed considerable restrictions on people's mobility, which affects the referral of chronically ill patients to health care structures. The emerging need for alternative ways to follow these patients up is leading to a wide adoption of telemedicine. We aimed to evaluate the feasibility of this approach for our cohort of patients with CTDs, investigating their attitude to adopting telemedicine, even after the pandemic. Methods: We conducted a telephonic survey among consecutive patients referred to our CTD outpatients' clinic, evaluating their capability and propensity for adopting telemedicine and whether they would prefer it over face-to-face evaluation. Demographical and occupational factors were also collected, and their influence on the answers has been evaluated by a multivariate analysis. Results: A total of 175 patients answered our survey (M/F = 28/147), with a median age of 62.5 years [interquartile range (IQR) 53–73]. About 80% of patients owned a device allowing video-calls, and 86% would be able to perform a tele-visit, either alone (50%) or with the help of a relative (36%). Telemedicine was considered acceptable by 78% of patients and 61% would prefer it. Distance from the hospital and patient's educational level were the strongest predictive factors for the acceptance of telemedicine ( P < 0.05), whereas age only affected the mastering of required skills ( P < 0.001). Conclusion: Telemedicine is a viable approach to be considered for routine follow-up of chronic patients, even beyond the pandemic. Our data showed that older patients would be willing to use this approach, although a proper guide for them would be required.